Irreversible evolution of dislocation pile-ups during cyclic microcantilever bending - Dávid Ugi; Kolja Zoller; Kolos Lukács; Zsolt Fogarassy; István Groma; Szilvia Kalácska; Katrin Schulz; Péter Dusán Ispánovity (Materials & Design, 2024)
In single crystals, plastic deformations are predominantly governed by dislocation movement and interactions. The group of dislocations that creates strain gradients, known as geometrically necessary dislocations (GNDs), also deterministically contributes to strain hardening, micron-scale size effects, fatigue, and Bauschinger effect. During bending large strain gradients naturally emerge which makes this deformation mode exceptionally suitable to study the evolution of GNDs. Here we present bi-directional bending experiment of a Cu single crystalline microcantilever with in situ characterisation of the dislocation microstructure in terms of high-resolution electron backscatter diffraction (HR-EBSD). The experiments are complemented with dislocation density modelling to provide physical understanding of the collective dislocation phenomena. We find that dislocation pile-ups form around the neutral zone during initial bending, however, these do not dissolve upon reversed loading, rather they contribute to the development of a much more complex GND dominated microstructure. This irreversible process is analysed in detail in terms of the involved Burgers vectors and slip systems. We conclude that at this scale the most dominant role in the Bauschinger effect and corresponding strain hardening is played by short-range dislocation interactions. The in-depth understanding of these phenomena will aid the design of microscopic metallic components with increased performance and reliability.